Synergistic use of gradient flipping and phase prediction for inline electron holography - Ozsoy-Keskinbora, Cigdem (2023)
Inline holography in the transmission electron microscope is a versatile technique which provides real-space phase information that can be used for the correction of imaging aberrations, as well as for measuring electric and magnetic fields and strain distributions. It is able to recover high-spatial-frequency contributions of the phase effectively but suffers from the weak transfer of low-spatial-frequency information, as well as from incoherent scattering. Here, we combine gradient flipping and phase prediction in an iterative flux-preserving focal series reconstruction algorithm with incoherent background subtraction that gives extensive access to the missing low spatial frequencies. A procedure for optimizing the reconstruction parameters is presented, and results from Fe-filled C nanospheres, and MgO cubes are compared with phase images obtained using off-axis holography.